75Se HCAT test in the detection of bile acid malabsorption in functional diarrhoea and its correlation with small bowel transit. Issue 8 (August 1987) - Sciarretta, G; Fagioli, G; Furno, A; Vicini, G; Cecchetti, L; Grigolo, B; Verri, A; Malaguti, P
Abstract : The purpose of this study was to evaluate whether bile acid malabsorption assessed by the 75SeHCAT test, had a pathogenetic role in functional chronic diarrhoea and to ascertain whether the small bowel transit time (SBTT) could be correlated with the 75SeHCAT test results. The test was based on the counting of the abdominal retention of a 75-selenium labelled homotaurocholic acid. The 75SeHCAT test was carried out in a control group of 23 healthy adults and in 46 patients, 38 of whom were suffering from irritable bowel syndrome (IBS) of diarrhoeic form and eight patients who had undergone cholecystectomy and were suffering from chronic diarrhoea. Faecal bile acid loss was determined in nine patients, and in 14, serum bile acid increase after a standard meal was measured. In 17, SBTT was studied by hydrogen breath test after lactulose administration (21 g in 300 ml water). In 15 patients, choledochocaecal transit time was estimated by Tc99m-HIDA (111 MBq) cholescintigraphy. In 20 of 46 subjects, 75SeHCAT retention was below normal level, and in 19 cholestyramine administration relieved diarrhoea. 75SeHCAT results were related to faecal bile acid loss, while no correlation was found with serum bile acids and SBTT. The data suggest a possible wider use of the 75SeHCAT test in chronic diarrhoea to estimate bile acid malabsorption in irritable bowel syndrome, diarrhoeic form, and provide an effective treatment. In our patients small bowel transit velocity does not seem to be a pathogenetic factor of bile acid malabsorption.